Effectiveness Of an Educational Program on Knowledge Regarding Cardiac Rehabilitation Among Post-Myocardial Infarction Patients Who Are Admitted to The Cardiac Inpatient Department at A Selected Cardiac Hospital - Dildar, Mohamad; Vashist, Suman; Ahmed, Nafees; Massey, Julia; Negi, Heena; Cherian, Blessy (Journal of Neonatal Surgery, 2025)
Introduction - This study evaluates the impact of an educational program on enhancing knowledge about cardiac rehabilitation among post-myocardial infarction patients. Conducted in the cardiac inpatient department of a selected hospital in Dehradun, it aims to assess whether targeted education improves patients' understanding of their recovery process. The findings will inform strategies to promote adherence to cardiac rehabilitation protocols. Ultimately, the study seeks to improve patient outcomes through increased awareness and engagement. Objectives: The main objective of the study is to evaluate the effectiveness of an educational program on knowledge regarding cardiac rehabilitation among post-myocardial infarction patients who are admitted to the cardiac inpatient department. Aim: The aim of this study is to evaluate the effectiveness of an educational program in enhancing knowledge about cardiac rehabilitation among post-myocardial infarction patients. It also aims to assess the program's impact on patients' understanding and participation in their recovery. Method: The study was conducted using a pre-experimental research design (one-group pre-test and post-test design). The sample consisted of 60 post-myocardial infarction patients from Shri Mahant Indiresh Hospital, Dehradun, Uttarakhand, India. Non-probability convenient sampling technique was used to select the participants for this study. Moreover, the tool used for this study was a structured knowledge questionnaire. Result: Results of the study indicated that the level of knowledge regarding cardiac rehabilitation showed that, during the pre-test, 44 (73.3%) of the post-myocardial infarction patients had moderately adequate knowledge, 12 (20%) had inadequate knowledge, and only four (6.7%) had adequate knowledge. After the intervention (educational program), there was an improvement in the level of knowledge; on the same day, all post-myocardial infarction patients, 60 (100%), had adequate knowledge. The study concluded that the mean and standard deviation of the level of knowledge regarding cardiac rehabilitation were 26.67 and 1.323, respectively. The t-value was 24.941 (59) at p<0.05, which indicates that the educational program was effective in improving the knowledge of post-myocardial infarction patients about cardiac rehabilitation. Conclusion: The study concluded that the educational program significantly improved post-myocardial infarction patients' knowledge about cardiac rehabilitation. This indicates that structured education is effective in enhancing patient understanding and engagement in their recovery process..